Some Observations on Lewis Mumford’s “The City in History” - David Riesman (Washington University Law Quarterly, 1962)
For a number of years I have not had any time to undertake book reviews but I feel so keenly the importance and excitement of Mumford's work, and my own personal debt to that work, that I wanted to contribute to this symposium even if I could not begin to do justice to the task. What follows are my only slightly modified notes made on reading selected chapters of the book-notes which I had hoped to have time to sift and revise for a review. I hope I can give some flavor of the book and of its author and invite readers into the corpus of Mumford’s work on their own.